2008
DOI: 10.1189/jlb.1207816
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses toPneumocystis murinaare robust in healthy mice but largely absent in CD40 ligand-deficient mice

Abstract: Pneumocystis is a pathogen of immunocompromised hosts but can also infect healthy hosts, in whom infection is rapidly controlled and cleared. Microarray methods were used to examine differential gene expression in the lungs of C57BL/6 and CD40 ligand knockout (CD40L-KO) mice over time following exposure to Pneumocystis murina. Immunocompetent C57BL/6 mice, which control and clear infection efficiently, showed a robust response to infection characterized by the up-regulation of 349 primarily immune response-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 69 publications
9
49
0
Order By: Relevance
“…These responses were temporally associated with the Pneumocystis organism load and peaked at approximately the same time as robust immune responses were detected by our earlier microarray studies (18). Of note, a higher proportion of cells produce IFN-␥ compared to IL-17, with the former accounting for ϳ25 to 30% of CD3 ϩ T cells compared to ϳ15% for the latter.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…These responses were temporally associated with the Pneumocystis organism load and peaked at approximately the same time as robust immune responses were detected by our earlier microarray studies (18). Of note, a higher proportion of cells produce IFN-␥ compared to IL-17, with the former accounting for ϳ25 to 30% of CD3 ϩ T cells compared to ϳ15% for the latter.…”
Section: Discussionmentioning
confidence: 48%
“…We initially characterized the frequency of NK cells, NKT cells, and ␥␦ T cells because our prior microarray studies in immunocompetent animals had suggested a potential role for these cells in early infection (maximum at ϳ14 days) (18). In three separate experiments, we analyzed these cell populations in animals that had been exposed for 7 to 24 days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations